Городища Пороської оборонної лінії Бушеве та Піщана. Топографічні та стратиграфічні дослідження - Манігда, О.В.; Борисов, А.В.; Беленко, М.М.; Пічкур, Є.В. (Археологія і давня історія України, 2021)
У статті представлені результати топографічних
обмірів, аналізу топографії, сучасного
стану пам’яток та приклад реконструкції стратиграфії укріплень на основі буріння. Висвітлено
основні кроки методики топографічного та стратиграфічного досліджень. This paper presents the results of topographic survey,
analysis of topography, current state of sites and
gives an example of stratigraphic reconstruction of
fortifications based on ground drilling. The main steps
of the methodology of topographic survey and stratigraphic
researches are highlighted.
The closest hillforts to the Sukholisy one were documented
by specialists of the Architectural and Archaeological
Expedition of Institute of Archaeology during
the campagne of 2020. The purpose of these works was
to document the current state of sites and to prepare
information for the conservation documentary.
Busheve hillfort is similar to the Sukholisy one by
its construction type and belongs to the early hillforts
in the defensive line of Ros River area (Porossia). The
study of this site is important for understanding the
initial stage of the Old Rus settlement structure of
Central Porossia region.
Due to the stratigraphic research the cross-section
of Busheve and Pishchana hillforts was reconstructed.
Analyzing the information obtained from the ground
drilling it is possible to make some conclusions for Busheve
hillfort: 1) the defensive constructions of this hillfort
were built in the river floodplain around a large dune;
2) the moat is traced only on one side; 3) drills 16—18
probably indicates the presence of archaeological layers
appeared before the hillfort constructions.
Conclusions by the results of drilling for Pishchana
hillfort are the following: 1) the moat was made by
deepening of the natural ravine; 2) the defensive wall
has the traces of repair; 3) drill 11 found that on the
edge of the hillfort the fortifications of World War II
period were bult.
The number of large-scale plans of Busheve and
Pishchana hillforts were made with all the necessary
descriptions and measurements with designation the
constructions of the hillforts; stratigraphic researches;
current state of hillforts; areas damaged by human activities.
They are made for the preparation of conservation
documentary.